Productividad laboral de los servidores públicos del Registro de la Propiedad en el gad del cantón Babahoyo - Cadena Benitez, Marilin Selene (2019)
The research carried out in the Property Registry Department of the GAD of the Babahoyo canton, aims to identify the main risk factors that affect productivity. To obtain the information, the methodology of applied research was used, which is composed of deductive and inductive methods, type of descriptive research, survey and questionnaire. The results obtained in the investigation reveal that in the Department of Property Registry, there is no adequate document management, since there have been errors regarding the delivery of property certificates, documentation deviations and little empathy of the public servant in the citizen attention. Therefore it is concluded that document management lacks prolixity in the organization of both physical and digital archives; enabling documentation for the continuity of the property registration process, a situation that impacts productivity levels and makes it impossible to provide a timely response to user requirements